2012 Frontiers in Education Conference Proceedings 2012
DOI: 10.1109/fie.2012.6462318
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and issues in the development of a Software Engineering simulation game

Abstract: In Software Engineering courses, students are introduced to important theories and concepts. However, these courses lack a practical opportunity for students to experience them more effectively. Even with the team-based project approach it is not possible to train students in all the real situations of a software development organization, due to the very nature of software applications and the large variety of organizational cultures. Simulation games are an appropriate complementary approach to the traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Students found it quite enjoyable, and they had fun during the game play. They learned new concepts and reinforced concepts taught in Software Engineering course [12], [13].…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Students found it quite enjoyable, and they had fun during the game play. They learned new concepts and reinforced concepts taught in Software Engineering course [12], [13].…”
Section: Model Validationmentioning
confidence: 99%
“…SPIAL is a graphical, interactive, and adaptable simulation game [12], [13], [14] (Figure 1). The game goal is to improve the Software Engineering learning, using simulation.…”
Section: Spialmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous experience has demonstrated that it is important to use simulation games complementary to other educational techniques, which should be accompanied by an adequate amount of direction and guidance given to the students [Peixoto et al 2012, Peixoto et al 2014. In the recent years, an increasing number of Software Engineering educational games can be found in the literature, e.g.…”
Section: Introductionmentioning
confidence: 99%